Eye contact perception in high-functioning adults with autism spectrum disorder. (January 2021) - Uono, Shota; Yoshimura, Sayaka; Toichi, Motomi
The present study investigated how the eye contact perception of ingroup and outgroup faces by Japanese adults with high-functioning autism spectrum disorder differed from that of age-, sex-, and IQ-matched typically developing individuals. The autism spectrum disorder and typically developing individuals were equally likely to perceive subtly averted gazes as self-directed gazes. In both groups, the frequency with which self-directed gazes were perceived decreased as gaze aversion increased. In general, individuals with autism spectrum disorder were equally capable of perceiving a self-directed gaze as typically developing individuals. However, typically developing individuals, but not individuals with autism spectrum disorder, were more likely to perceive self-directed gazes from ingroup faces than from outgroup faces. Stimuli ratings revealed that individuals with autism spectrum disorder, but not those with typically developing, gave higher warmth ratings to ingroup faces with averted gazes and outgroup faces with direct gazes compared to other types of face stimuli, suggesting atypical affective experiences in response to ingroup and outgroup faces in autism spectrum disorder. These results suggest that individuals with autism spectrum disorder did not show an ingroup bias for the perception of a self-directed gaze, and raise the possibility that an atypical emotional experience contributes to the diminished ingroup bias for the perception of a self-directed gaze. Lay abstract: The detection of a self-directed gaze is often the starting point for social interactions and a person who feels as if they are being watched can prepare to respond to others' actions irrespective of the real gaze direction because the other person may likely be motivated to approach. Although many studies demonstrated that individuals with autism spectrum disorder have difficulty discriminating gaze direction, it remains unclear how the perception of self-directed gaze by individuals with autism spectrum disorder differs from that of age-, sex-, and IQ-matched typically developing individuals. Participants observed faces with various gaze directions and answered whether the person in the photograph was looking at them or not. Individuals with and without autism spectrum disorder were just as likely to perceive subtle averted gazes as self-directed gazes. The frequency of perceiving a self-directed gaze decreased as gaze aversion increased in both groups and, in general, individuals with autism spectrum disorder showed a comparable ability to perceive a self-directed gaze as that of typically developing individuals. Interestingly, considering face membership of photographs (ingroup or outgroup faces), typically developing individuals, but not individuals with autism spectrum disorder, were more likely to perceive self-directed gazes from ingroup faces than from outgroup faces. However, individuals with autism spectrum disorder had different affective experiences in response to ingroup and outgroup faces. These results suggest that individuals with autism spectrum disorder did not show an ingroup bias for the perception of a self-directed gaze, and raise a possibility that an atypical emotional experience contributes to the diminished ingroup bias.